2015
DOI: 10.5194/acp-15-9313-2015
|View full text |Cite
|
Sign up to set email alerts
|

Particulate organic nitrates observed in an oil and natural gas production region during wintertime

Abstract: Abstract. Organic nitrates in both gas and condensed (aerosol) phases were measured during the Uintah Basin Winter Ozone Study from January to February in 2012. A high degree of correlation between total aerosol volume at diameters less than 500 nm and the particulate organic nitrate concentration indicates that organic nitrates are a consistent, if not dominant, fraction of fine aerosol mass. In contrast, a similar correlation with sub-2.5 µm aerosol volume is weaker. The C : N atomic ratio inferred from fiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Although little is known about the health impacts of pON, inhalation of nitrating reagents in aerosol is thought to be associated with various health risks such as the triggering of immune responses and promoting the genesis of allergies (Pöschl, 2005). Furthermore, pON can be highly functionalized, which has been observed in the events of new particle formation and secondary organic aerosol (SOA) growth (Ehn et al, 2014;Lee et al, 2016), with strong impacts on air quality and climate (Hallquist et al, 2009;Kanakidou et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although little is known about the health impacts of pON, inhalation of nitrating reagents in aerosol is thought to be associated with various health risks such as the triggering of immune responses and promoting the genesis of allergies (Pöschl, 2005). Furthermore, pON can be highly functionalized, which has been observed in the events of new particle formation and secondary organic aerosol (SOA) growth (Ehn et al, 2014;Lee et al, 2016), with strong impacts on air quality and climate (Hallquist et al, 2009;Kanakidou et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Low concentrations are found in remote regions and during the day. EURAD-IM simulations for Europe show an increase of SOA by 50 to 70 % when considering SOA formation by NO 3 oxidation with maximum ground-level concentrations of SOA from NO 3 oxidation in the range of 2 to 4 µg m −3 (Li et al, 2013;.…”
Section: Western United Statesmentioning
confidence: 99%
“…Extensive field investigations demonstrate the significant formation of pON via nocturnal NO3 radical chemistry of biogenic VOCs on a global scale (Kiendler-Scharr et al, 20 2016;Ng et al, 2017). Daytime production of pON has also been observed in urban and forested regions (Farmer et al, 2010;Kiendler-Scharr et al, 2016;Lee et al, 2016;Lee et al, 2015b) but the potential role of anthropogenic VOCs in pON formation remains largely unexplored. Until recently, a field study Atmos.…”
Section: Introductionmentioning
confidence: 99%
“…Discussion started: 11 January 2019 c Author(s) 2019. CC BY 4.0 License. demonstrated that oil and natural gas drilling operations were associated with alkane-derived pON production (Lee et al, 2015b). Heavier saturated alkanes were more important contributors to pON formation from OH radical oxidation during the daytime, whereas pON from lighter biogenic VOCs dominated nighttime production due to NO3 and N2O5 chemistry (Lee et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation